SLR Systematic Literature Review: The Impact of Independent Curriculum Changes on Higher Education in Indonesia - Imleesh, Mohammed Mahmoud (Unram Journal of Community Service, 2025)
The curriculum serves as a foundational element of education, significantly influencing the achievement of educational goals and the overall success of various sectors and settings. In light of the curriculum reforms initiated in 2020, it is imperative to understand their implications for educational institutions and the anticipated outcomes of the new curriculum policy. This study employs a comprehensive Literature Review methodology, utilizing the PRISMA framework to systematically analyze 22 scholarly articles and journals. The findings of this research indicate that the recent changes in secondary education have a markedly positive impact on the educational landscape in Indonesia. These reforms are designed to align with the principles of Society 5.0, which emphasizes the integration of advanced technology and human-centric approaches. As a result, the new curriculum fosters an environment that promotes creativity, innovation, and critical thinking among students. This study not only highlights the transformative potential of the curriculum changes but also underscores the necessity for ongoing adaptation and responsiveness to the evolving educational needs of society.